Jan Arends : verzameld werk - Arends, Jan, 1925-1974; Van Weringh, Koos (Jacobus), 1934-; Wierema, Thijs, 1944- (Amsterdam : De Bezige Bij, 1984)
Het verzamelde werk van de Nederlandse schrijver, dichter en vertaler Jan Arends.